2005
DOI: 10.1007/s11183-005-0012-y
|View full text |Cite
|
Sign up to set email alerts
|

Flavones in genetically transformed Scutellaria baicalensis roots and induction of their synthesis by elicitation with methyl jasmonate

Abstract: The composition and content of flavones were estimated in pRi T-DNA-transformed skullcap ( Scutellaria baicalensis Georgi) roots obtained by the inoculation of axenically grown seedlings with a wild A4 strain of the soil bacterium Agrobacterium rhizogenes. It was elucidated by analytical and preparative HPLC of phenolic compounds in the extracts from the pRi T-DNA-transformed roots and also by ultraviolet spectroscopy and 1 H and 13 C NMR that cultured skullcap roots contained similar basic flavones as intact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 20 publications
1
18
0
Order By: Relevance
“…8‐ O ‐Methyl transferase is probably involved in the formation of wogonin from nor‐wogonin . The data about transformations of the flavones themselves exist as well, in particular, according to the glucuronides‐aglycones pathway, where the endogenous β ‐glucuronidase and UDP glycosyltransferases participate …”
Section: Introductionsupporting
confidence: 60%
“…8‐ O ‐Methyl transferase is probably involved in the formation of wogonin from nor‐wogonin . The data about transformations of the flavones themselves exist as well, in particular, according to the glucuronides‐aglycones pathway, where the endogenous β ‐glucuronidase and UDP glycosyltransferases participate …”
Section: Introductionsupporting
confidence: 60%
“…Further work by Kuzovkina et al (2005) found that the flavonoid content of cultures of transformed roots were threefold lower than in the roots of intact (untransformed) 5-yr-old plants. They also showed that flavonoid ratios in roots cultured on B5 or MS media changed but the overall concentration remain unchanged and treatment of 3-wk-old cultured roots with methyl ether of jasmonic acid (MeJa), a stress response, doubled the total concentration of major flavones (Kuzovkina et al 2005). Recent work by Hwang (2006) evaluated and maximized the root growth and baicalin content of hairy roots on Schenk and Hildebrandt medium supplemented with 4 or 6% sucrose.…”
Section: Scutellaria: a Model For Application Of Biotechnology To Medmentioning
confidence: 97%
“…Kovacs et al (2004) developed liquid chromatographic methods for determination of the main flavonoid contents of hairy roots cultures and found that the baicalin and wogonin content of transformed roots was consistently higher than intact plants from Siberia (Kovacs et al 2004). Further work by Kuzovkina et al (2005) found that the flavonoid content of cultures of transformed roots were threefold lower than in the roots of intact (untransformed) 5-yr-old plants. They also showed that flavonoid ratios in roots cultured on B5 or MS media changed but the overall concentration remain unchanged and treatment of 3-wk-old cultured roots with methyl ether of jasmonic acid (MeJa), a stress response, doubled the total concentration of major flavones (Kuzovkina et al 2005).…”
Section: Scutellaria: a Model For Application Of Biotechnology To Medmentioning
confidence: 99%
“…THB was synthesized from D-glucose as a starting material, phytic acid, being a cheap and abundant byproducts of many grains, can also be used as a starting material [67]. In this three-step method, Dglucose, as a carbon source, was biocatalytically converted to myo-inositol (32) or myo-inositol-1-phosphate, using recombinant E. coli or Saccharomyces cerevisiae that encodes the enzyme myo-inositol-1-phosphate synthase. Oxidation of myo-inositol, exploiting recombinant Bacillus subtilis or Gluconobacter oxydans that encodes the enzyme inositol dehydrogenase led to formation of myo-2-inosose (33), 95% yield.…”
Section: Bioengineered Synthesis Of Thbmentioning
confidence: 99%
“…In addition, methyl jasmonate was reported to enhance arachidonic acid-induced resistance against microorganisms in some plants [31]. In other experiments, methyl jasmonate considerably increased the concentration of major flavones, which have pronounced antimicrobial activity [32].…”
Section: Introductionmentioning
confidence: 95%